PENINGKATKAN MOTIVASI DAN HASIL BELAJAR FISIKA ( ALAT-ALAT OPTIKA) SISWA SMAN 1 BANTUL DENGAN PEMBELAJARAN INKUIRI - Sri Suparwati (Jurnal Riset Daerah, 2023)
This research aims to increase the motivation and learning outcomes of physics in the Optical Instruments material for class This research was carried out in two cycles. Each cycle consists of three meetings. The subjects of this research were all students of class Data sources are the results of teacher observations of teaching, learning, motivation questionnaires, student responses, and student learning outcomes. The research instruments used have been tested for validity and reliability, so they can be used as research instruments. The results of the research are that the inquiry learning model can increase students' motivation and physics learning outcomes in the Optical Equipment material. Motivation result data in cycle I was: 88.66% and in cycle II was: 80.15%. This result is in the high category, when compared with the initial condition, student motivation was: 50%. Meanwhile, the average score for physics learning outcomes in cycle I: 83 and in cycle II: 86. So it can be concluded that the inquiry learning model can increase motivation and physics learning outcomes in the Optical Equipment material for class XI SMA.